2000
DOI: 10.1242/jcs.113.5.795
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin fragments induce MMP activity in mouse mammary epithelial cells: evidence for a role in mammary tissue remodeling

Abstract: Mammary gland form and function are regulated by interactions between epithelium and extracellular matrix. Major glycoprotein components of extracellular matrix have been identified that give survival, proliferation and differentiation signals to mammary epithelial cells. We provide evidence that proteolytic fragments of the extracellular matrix glycoprotein, fibronectin, suppress growth and can promote apoptosis of mouse mammary epithelial cells. During mammary gland involution, total fibronectin and fibronec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…HOCl-modified HSA also modulates immune-cell function (reviewed [ 3 , 6 , 70 ]), with exposure to the modified protein reported to elevate oxidant formation by stimulating neutrophil activation and degranulation at sites of inflammation [ 71 , 72 ]. Other studies have reported that fibronectin fragments (potentially arising from oxidant or enzymatic degradation) and cryptic domains in the α1-chain of laminin-1 exposed by structural changes can induce cellular MMP expression [ 73 , 74 ]. Thus, oxidant formation can result in a feed-forward loop (“vicious cycle”) of increasing MMP expression, release, activation, ECM damage and further activation cycles, with this driven by the synergistic effects of oxidant formation, MMP activation and the further proteolysis of additional proMMP by the oxidant-activated enzyme ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…HOCl-modified HSA also modulates immune-cell function (reviewed [ 3 , 6 , 70 ]), with exposure to the modified protein reported to elevate oxidant formation by stimulating neutrophil activation and degranulation at sites of inflammation [ 71 , 72 ]. Other studies have reported that fibronectin fragments (potentially arising from oxidant or enzymatic degradation) and cryptic domains in the α1-chain of laminin-1 exposed by structural changes can induce cellular MMP expression [ 73 , 74 ]. Thus, oxidant formation can result in a feed-forward loop (“vicious cycle”) of increasing MMP expression, release, activation, ECM damage and further activation cycles, with this driven by the synergistic effects of oxidant formation, MMP activation and the further proteolysis of additional proMMP by the oxidant-activated enzyme ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transmembrane receptor proteins of the integrin family mechanically couple the actin cytoskeleton to the ECM by binding to Fn1 and other adhesion molecules, such as collagen and vitronectin. A convincing body of evidence suggests that MMP activation and expression is triggered by interaction of the cell adhesion molecule Fn1 or its proteolytic fragments with integrins (Esparza et al, 1999;Schedin et al, 2000;Yan et al, 2000;Thant et al, 2001;Forsyth et al, 2002;Loeser et al, 2003;Jin et al, 2011). This interaction can be inhibited by the RGD peptide (Koivunen et al, 1995), a tripeptide domain located in the 10th type-III module of Fn1 and site of cell attachment via b1 integrins.…”
Section: Discussionmentioning
confidence: 99%
“…During postpartum involution, significant remodeling occurs in the ECM. , Differential ECM protein synthesis occurs in various cells within the organ and several secreted proteases become activated resulting in active matrix remodeling. ,, ECM can be biochemically isolated from the mammary gland and utilized both in vitro and in vivo to assess effects on tumor cell behavior . ECM isolated from actively involuting mammary glands consistently promotes an invasive tumor cell phenotype in 3D culture assays and tumor growth and metastasis in xenograft tumor models when compared to ECM isolated from nulliparous rats. ,, However, ECM isolated from mammary glands of rats treated with ibuprofen during involution demonstrated reduced tumor promoting attributes; phenocopying mammary ECM from the nulliparous rather than the involuting gland .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Differential ECM protein synthesis occurs in various cells within the organ and several secreted proteases become activated resulting in active matrix remodeling. 15,22,23 ECM can be biochemically isolated from the mammary gland and utilized both in vitro and in vivo to assess effects on tumor cell behavior. 24 ECM isolated from actively involuting mammary glands consistently promotes an invasive tumor cell phenotype in 3D culture assays and tumor growth and metastasis in xenograft tumor models when compared to ECM isolated from nulliparous rats.…”
Section: ■ Introductionmentioning
confidence: 99%